Redefining The Concept of Consumer Switch Intention: A Literature Review - Satriadi, Satriadi; Anggraini, Nia; Alhempi, R. Rudi; Risnawati, Risnawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The aim of this paper is to redefine building switching intentions by analyzing the concept of consumer switching intentions. The study of consumer switching intentions was carried out by identifying the definition of consumer switching intentions. The problem raised in this paper consists of the perception of switching intention which consists of different definitions of switching intention from each research result (Gupta et al., 2004), (Anton et al., 2007), (Nikbin et al., 2013), (CN Lin & Wang, 2017), (Liang et al., 2018), (Aw & Chong, 2019), and (BÃ¶len, 2020). This paper takes the method of comparing the concept of consumer switching intentions from many researchers who have had their research validated. The ramifications of this study's findings will serve as a point of reference for a number of investigations, resulting in the identification of each definition of consumer switching intents. This paper's unique contribution will redefine the concept of consumer switching intent.